The Profile of the Organized Industrial Zones in Kocaeli/TURKEY - Zeynep Gamze Mert; Gülşen Akman (European Regional Science Association (ERSA), 2011)
The industry was determined to be "locomotive sector" in the planned development period starting in 1960 in Turkey and long-term targets have been set such as providing economic balance, realizing economic and social development. But after 1980's, because of the fast industrialization and urbanization some environmental problems emerged in the Turkish cities. So, in industrial development, the Organized Industrial Zones implementations were started to discipline the industrial areas, contribute to planned development of the city and reduce the environmental effects of the industry. Kocaeli is the most industrialized city which is situated in the east and 90 km far from Istanbul in Turkey. Kocaeli has always been a center of attraction for industrial investments due to its position on the road, sea and railway networks connecting Europe to Anatolia and near the major cities as Bursa and Istanbul. Today, there are 13 Organized Industrial Zones in Kocaeli. But these 13 Organized Industrial Zones are not efficient and effective in the industrial development. A lot of industrial establishments have still located in the city. The aim of this study is to determine the profile of the 13 Organized Industrial Zones in Kocaeli by exploring and comparing their locations, sectors, capacities, services and infrastructures. This profile will be helpful to develop the displacement demands and preferences of the industrial establishments and the industrial sustainability in Kocaeli.
Keywords: 330; Industrial development; industrial sustainability; Organized Industrial Zones; Turkey; Kocaeli